Synergization of yield strength and ductility for a dilute Mg-Zn-Nd-Ca alloy through pinned twin boundary and Guinier–Preston zone - Xin Wan; Maolin Yin; Chao Zeng; Weilin Liu; Peng Peng; Linsong Zhang; Bi Jia; Jianyue Zhang; Qingshan Yang; Qingwei Dai (Journal of Magnesium and Alloys)
Mg-Zn-RE alloys typically exhibit non-basal texture, weak dispersion hardening, and low yield strength. In this study, we designed a dilute quaternary Mg-0.6Zn-0.4Nd-0.2Ca (wt.%) alloy. Then, applied pre-strain and heat treatment to investigate the balance of yield strength and ductility via solute atom segregation at twin boundaries and nanophase modifications. The results indicated that Zn and Nd elements tend to co-segregate at the twin boundary, while Ca element segregates alone and presents a discontinuous distribution. Nanoscale precipitates of (Mg, Zn)3Nd and Mg2Ca with the size of 5∼20 nm underwent significant preferential precipitation at the twin boundary. Moreover, compared with Ca atoms, Zn atoms tend to combine with Nd atoms more preferentially towards the stacking faults, thereby forming a high-density monolayer Guinier-Preston (G.P.) zone. The segregation and precipitation of solute atoms at the twin boundary and the stacking faults increased the friction stress of twinning dislocations and lattice dislocations, thus improving the strength. Pinned twin boundaries facilitate the transition from basal 〈a〉 slip to pyramidal 〈c + a〉 slip due to the small geometrical compatibility factor (m′) value as well as the Schmid factor (SF) incompatibility. As a result, the pre-strained and heat-treated specimen's yield strength exhibits a 141% increase relative to the initial state specimen, accompanied by a modest improvement in ductility. The mechanism of multi-element segregation and precipitation at twin boundaries, and G.P. zone formation was discussed in detail.